Impact of gate current on the operational transconductance amplifier designed with nanowire TFETs - de M. Nogueira, Alexandro; G.D. Agopian, Paula [UNESP]; Simoen, Eddy; Rooyackers, Rita; Claeys, Cor; Collaert, Nadine; Martino, Joao A. (Elsevier, 2021)
An Operational Transconductance Amplifier (OTA) designed with SiGe-source nanowire Tunnel-FETs is presented and compared with OTAs designed with Si nanowire (NW) TFETs and Si NW MOSFETs with and without the effect of gate current (IG). The devices were modeled using Verilog-A language through lookup tables obtained by experimental data and they were used to simulate the OTA circuits. It was observed that, when the IG is negligible, there is a trade-off between the DC open loop gain (AV0) and the gain-bandwidth product (GBW) of these circuits. The Si NW MOSFET OTA presented the lowest AV0 (52 dB) but the largest GBW (9.5 MHz). The largest gain was obtained by the Si NW TFET (97 dB) but it also presents the lowest GBW (30 kHz). The SiGe-source TFET stands in the middle, with an AV0 of 88 dB and a GBW of 715 kHz. However, when IG is not negligible and included in the model, the gain of the TFET OTAs decreases considerably, down to 38.3 dB in the case of the Si TFET and down to 52.6 dB in the case of the SiGe-source TFET. This decrease in gain is mostly caused by an alteration in the desired bias point in the second stage of the OTA due to the change of the output voltage and bias currents. This issue possibly can be mitigated by using circuit design strategies. Nevertheless, the SiGe-source TFET OTA is less impacted by the gate current than the Si TFET OTA and still presents a larger gain than the Si NW MOS OTA (52.6 dB against 50 dB) when the IG is considered.
Keywords: Analog circuits; Gate current; Lookup table; Nanowire; OTA; SiGe; Tunnel-FET